Microbactérias não tuberculosas : aspectos clínicos e epidemiológicos e análise de espécies identificadas pela metodologia PRA - Castro, Elcineide Soares de (2012)
Infections caused by nontuberculous mycobacteria (NTM) are becoming more frequent around the world and also in Brazil. The ability of produce disease is clearly documented in the literature and its importance has been increasing steadily. Although mycobacteria can affect any human organ, the most common form of involvement is the lung disease. This study aimed to evaluate clinical and epidemiological characteristics of patients with NTM lung disease and the diversity of species isolated. We studied retrospectively 59 patients enrolled for treatment at the outpatient clinic reference Messejana Hospital, from 1998 to 2008. The species of NTM isolated from sputum were identified using PRA method in the Microbiology Laboratory, Faculty of Medicine, Federal University of Ceará. The variables studied were: year of diagnosis, age, origin, gender, profession and biological risk of illness, education level, family income, clinical symptoms, comorbidity, previous history of tuberculosis (TB), radiological findings, anti-HIV serology, tuberculin test, history of smoking and alcoholism and outcome. The quantitative and categorical variables were analysed by calculating frequencies and proportions of the measures of central location and dispersion for each variable separately. The analyzes of associations were performed using the nonparametric Pearson’s test and parametric test of the likelihood ratio (based on product binomial distributions / multinomial) using CI = 95% and p < 0,05. The PRA method identified all 59 species, with predominance of the following: M. abscessus, 28.5% (17/59); M. lentiflavum 18.6% (11/59); M. avium, 16.6% (10/59); M. fortuitum and M. smegmatis, 10.2% (06/59) each; M. kansasii, 6.8% (4/59). The mean age ± SD of the group was 50.4 ± 16.1 years; 62.7% (37/59) were male and 62, 7% had at most basic education, 72.9% (43/59) with income below the poverty level, 49.2% (29/59) reported using alcohol and 40.6% (24/59) smoking, 59.3% (35/59) were involved with biological risk, 86% (51%) lived in Fortaleza. Cough was observed in 91.5% (54/59) and expectoration in 72.9% (43/59). Fibrosis and cavity were in 71.2% (42/59) and 45.8% (27/59) of the patients, respectively. HIV serology was positive in 7% (4/59), tuberculin skin test was performed in only 22% (13/59), of which 92.3% (12/13) were positive, 54% (32/59) had cured and 15.3% (9/59) had died. The associations between the variable profession with biological risk and gender (60% female), and between profession with biological risk and comorbidity (75% had associated disease), and profession with biological risk and family income proved to be significant. The association analysis of the groups of species of NTM isolated, if potentially pathogenic or rarely pathogenic with the others different study variables were not significant, thus did not discriminate to differentiate the groups. This study demonstrated the importance for the recognition of NTM lung disease whose species can be identified in sputum samples and for the epidemiological importance and the need for differential diagnosis in cases of tuberculosis.